Two boys kissing - Levithan, David (Alfred A. Knopf, 2013)
A chorus of men who died of AIDS observes and yearns to help a cross-section of today's gay teens who navigate new love, long-term relationships, coming out, self-acceptance, and more in a society that has changed in many ways.